2015
DOI: 10.17696/2318-3691.22.3.2015.239
|View full text |Cite
|
Sign up to set email alerts
|

Ingestão Alimentar, Perfil Bioquímico E Estado Nutricional Entre Vegetarianos E Não Vegetarianos

Abstract: ResumoIntrodução: A dieta vegetariana tem sido associada a inúmeros benefícios à saúde. Objetivo: Comparar ingestão alimentar, perfil lipídico, glicemia, pressão arterial e antropometria entre adultos vegetarianos e onívoros. Casuística e Métodos: Foram selecionados 20 vegetarianos e 22 onívoros. A ingestão alimentar foi avaliada pelo recordatório de 24 horas. Foram analisados perfil lipídico e glicemia, além da aferição da pressão arterial e antropometria (circunferências do braço e cintura, prega cutânea tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
1
0
13

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 14 publications
0
1
0
13
Order By: Relevance
“…The low intake of these two fatty acids was associated with an increased risk of low birth weight infants in the Southern Indian study population [18]. On the other hand, comparing the diet of omnivores and vegetarians, an inner-city study on adults in the São Paulo region found a higher intake of polyunsaturated fatty acids among the vegetarian population [19]. Thus, national studies to investigate the intake of omega-3 polyunsaturated fatty acid and the balance between omega-3 and omega-6 intake, in subgroups of pregnant women with different eating styles, are required.…”
Section: Discussionmentioning
confidence: 90%
“…The low intake of these two fatty acids was associated with an increased risk of low birth weight infants in the Southern Indian study population [18]. On the other hand, comparing the diet of omnivores and vegetarians, an inner-city study on adults in the São Paulo region found a higher intake of polyunsaturated fatty acids among the vegetarian population [19]. Thus, national studies to investigate the intake of omega-3 polyunsaturated fatty acid and the balance between omega-3 and omega-6 intake, in subgroups of pregnant women with different eating styles, are required.…”
Section: Discussionmentioning
confidence: 90%
“…O mesmo grupo apresentou também o maior percentual de consumo excessivo, em 20% dos participantes. Resultados similares a esses foram observados por Ribeiro et al (2015), em que a adequação do consumo de carboidratos entre vegetarianos foi de 57,18%. Estudos relatam que quando comparados com indivíduos onívoros, os vegetarianos consomem significativamente mais energia na forma de carboidratos, em torno de 60% do valor calórico total.…”
Section: Discussionunclassified
“…Em relação ao consumo do grupo das hortaliças, apenas 6,7% dos indivíduos atingiram a recomendação. Já no estudo de Ribeiro et al (2015), os resultados foram superiores, sendo que 15% da amostra atingiu a recomendação. Em outro estudo feito por Couceiro, Slywitch e Lenz (2008), observou-se o consumo insuficiente em 85% do grupo quanto à verduras e legumes, resultados estes que não eram esperados pelo pesquisador, visto que a base da dieta vegetariana deveria ser de grãos e cereais, frutas, hortaliças, leguminosas e oleaginosas.…”
Section: Discussionunclassified
See 2 more Smart Citations